The antibacterial properties of Schizophyllum commune and Theobroma Cacao L / Mansur, N. A., Mahamud, R. A. and Nooh, H. M - N. A., Mansur; R. A, Mahamud; H. M, Nooh (Faculty of Plantation and Agrotechnology, 2023)
Natural products consist of their own properties where it can inhibit bacteria from growing. Split gill mushroom content of alkaloids, terpenoids, and flavonoids, while cocoa have polyphenols made up of flavonoids and non-flavonoids. These bioactive components discovered in split gill mushroom and cocoa have an important function as antibacterial agents. The purpose of this study is to investigate the impact of natural products in suppressing selected Gram positive and Gram-negative bacteria that might cause damage to humans. Kirby-Bauer disc diffusion was used to test antibacterial activity. The results indicated that the extract of split gill mushroom had the highest inhibitory zone against E. coli (21 mm) and S. aureus (11 mm), whereas the extract of cocoa had the least inhibitory zone with E. coli (13 mm) and S. aureus (10 mm). The achieved results indicated that split gill mushroom was the best natural product with antibacterial properties, followed by cocoa oil.